جواب الاستفهام بالاستفهام في البيان النبوي عبر الخطاب النسوي: Arabic rhetoric in the prophetic hadith - MUHAMMAD LAWAL AL-IMAM, UMAR (Nady Al-Adab : Jurnal Bahasa Arab, 2024)
ABSTRACT: This research aims to address rhetorical secrets in the context of the following the answer to the question by interrogation or repetition of its image in its various purposes, in order to clarify the rhetorical witticism as contained in the message of Prophet Muhammad. The rhetorical witticism took the greatest share among the methods used by the chosen Prophet in the divine mental content which contained folds of phenomena that called for contemplation into its depth in order to realize its aims and goals which can be detected and acquired by the eloquent. Hence, this method was endorsed and recommended by scholars, because it is a great art of expression cherished by all a sundry which reveals hidden meanings, and presents them in a wonderful way that suits the souls and emotions. No doubt, this leads the heart and feeling to maximum enjoyment, and the mind to artistry creativity which shows you the meanings in hidden exhibitions, bright colors, and varying testes, so that the souls, including the faculties of perception, become a highly sensitive to the extent that meanings are reflected via them, and consequently, understood by the minds and hearts before insights and visions. That is why the question of the rhetoricians and critics was held in high esteem. The rhetoricians monitor the images of rhetorical questions and define their goals, while on the other hand the critics reveal its impact on the genres of literature and the arts of fine expression. In lieu of the above, the importance of the article is embodied in studying this method in the consideration of the selections of the hadiths of the Prophet in the shadows of addressing the female gender over the following models: Keywords: The phenomenon of interrogative answering, characteristics of the prophetic statement, masterpieces of thought in feminist discourse.